Methodical aspects of using of Web 2.0 services in the process of blended learning - Diana V. Moglan (Открытое образование (Москва))
The article is devoted to the issues of organization of blended learning using Web 2.0 services intended at providing educational services via the Internet. The learning process is designed by implementing learning technologies based on the active work of students, including cooperation, joint creativity and the development of personally significant Internet resources. At the same time, students interact with the instructor in an active form both internally and remotely. The effectiveness of mastering the course by students in the process of blended learning depends on the ratio of the forms of study used (classroom work, independent work (individual, group), distance interaction) and the nature of the information presented for classroom and independent work. The problem of finding the optimal combination of forms, methods and means of training is one of the key to providing a holistic learning process.The purpose of this work is to consider the methodological aspects of the organization of blended learning using Web 2.0 services to improve the quality of educational services and motivate students to perform various types of educational activities.The main part of the article considers with the educational opportunities of the most popular Web 2.0 services, the pedagogical features and the nature of the implementation of study assignments in the process of blended learning, identifies the specifics of implementing joint activities in the Internet, and determines the approaches to organizing the network interaction of the teacher and students. Web 2.0 services were used to organize open access to the information resources of the course and the personal information space of students, to discuss issues collectively and to collaborate with students on the training project, to provide prompt and reliable communication between students and the teacher, passing tests and interviews to identify the intermediate level knowledge or to determine the attitude of students to some problem. As a theoretical basis for the organization and maintenance of blended learning using Web 2.0 services was used a five-step model of moderating online learning by J. Salmon (access and motivation, online socialization, information exchange, knowledge building, development). The article gives an example of the practical implementation of J. Salmon’s model using Web 2.0 services (blogs, social photo and video services, social bookmarking services, social networking services, etc.).After completion of the training, students were questioned (32 participants) in order to establish their attitude to the use of Web 2.0 services in the learning process. As a result of the performed research, the effectiveness of the proposed methodological approaches to the organization of blended learning has been confirmed. The analysis of the obtained results showed that the process of network interaction is determined by the high level of students’ interest in this activity, the social involvement of students in it, the desire to present their point of view on the problem that has arisen, to justify and prove it to other members of the discourse.